Large Bowel Obstruction following Endoscopic Spray Cryotherapy for Palliation of Rectal Cancer Bleeding. Issue 1 (2017) - Prakash, Ravi; Gupta, Digant; Vashi, Pankaj
ABSTRACT : N/A: We report a unique case of a 79‐year‐old woman with metastatic rectal cancer who developed bowel obstruction following endoscopic cryotherapy with liquid nitrogen for palliation of bleeding in the rectum. She developed abdominal distention and pain following the procedure. Computed tomography of the abdomen revealed a paraumbilical hernia containing a segment of transverse colon resulting in partial bowel obstruction. It appears that the recurrent freeze‐thaw cycles with poor decompression of the colon despite active venting suction during cryotherapy may have resulted in bowel distention and collapse, causing conformational changes resulting in partial bowel obstruction due to a paraumbilical hernia.